Phutthatham phư̄a songsœ̄m sētthakit - Kǣo Chittakhop (Fāi Phœ̄iphǣ Phraphutthasātsanā, Kō̜ng Phutthasāsanasưksā, Samnakngān Phraphutthasātsanā hǣng Chāt, 2007)
Buddha-dhamma, the Buddha's teachings, for socio-economic promotion and development in Thailand.